' Customers satisfaction towards the effectiveness of order cycle time management at perodua parts sales department / Rohana Bulat - Bulat, Rohana (2019)
Responding to the rapidly changing in automobile business nowadays, Perodua Sdn. Bhd. has grown tremendously to become one of the well known second National car company and spare parts sales company, which provide a wide range of services in order to satisfy customer needs and expectation. In order to compete, with other potential automobile spare parts selling department which offers various efficient services, Perodua Parts Sales Department (PPSD) also not leave behind to offer one of their efficient service in managing more than 3000 spare parts components. This study will try to explore the management of order cycle time activities practice by PPSD focusing on time management in completing order till its delivery services. This research is conducted to get feedback from Perodua customers and dealers at Perodua Parts Department (PPSD) Head Office Parts Department. Furthermore, this research could help the company to find out whether their order cycle time management is effective and efficient compared to other automobile spare parts department. The result also would be the basic information for further assumptions and recommendation to be acknowledge by the researcher and the management of order cycle at PPS D. Literature review provides in Chapter 2 are statement written or said before about the main topic of research. It will give extra knowledge and for more easy understanding. Topic touch is Perodua Sdn. Bhd. Today, Perodua Parts Order Cycle Management, Customers Satisfaction, Customers Service, Order Management, Speed Communication, Documentation and Stock Availability. This scope of study will emphasizes on how PPSD using the elements of order cycles in meeting customer expectation on time. This research will cover on the effective time management during documentation processing, stock availability, order processing, management, speed of communication and accurate delivery of order. 100 questionnaires were distributed to dealers and cash customers for these study purposes. Findings and analysis is done using basic manual percentage calculation and SPSS (Statistic Package for Social Science Package). From the result it was found that there is lack of order cycle time management practices by PPSD and not satisfactory meet customer expectation time. Finally the report, include a conclusions and some recommendations which might be useful for the management of PPSD to improve and making changes to the order cycle time management in order to meet customers satisfaction and quick order completing requirement.